Comparison of mother with father of children with cancer in terms of marital intimacy, parental self-efficacy and cognitive emotion regulation strategies - Gharehdaghi , Minoo; Kachooei , Mohsen (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was conducted with the aim of comparing mothers and fathers of children with cancer in terms of marital intimacy, parental self-efficacy and emotion regulation strategies. Method: This study was of comparative causal type. Among the parents who referred to Mahak Hospital in Tehran in 2022, 146 people (73 couples) were selected as the current sample and questionnaire of intimacy-marriage (Walker and Thompson, 1983), parental self-efficacy (Dumka et al., 1996) and cognitive emotion regulation strategies (Garnefski & Kraaij, 2006) were completed. Dependent t-test and SPSS-27 software were used to analyze the data. Results: The results showed that the average of marital intimacy and parenting self-efficacy was slightly higher in fathers than in mothers, but this difference was not statistically significant (p<0.05). However, in the cognitive emotion regulation strategies, mothers’ scores in the less important subscale of a number of adaptive strategies were higher than fathers’ and the mean rumination of maladaptive strategies was higher in fathers than in mothers. Therefore, in the comparison of fathers and mothers of children with cancer, no significant difference was found in terms of marital intimacy and parental self-efficacy, there was only a difference in cognitive emotion regulation strategies, compromised strategies and non-compromised strategies between fathers and mothers, which could mean that the performance of both parents depend on each other and act very similar to each other. Conclusion: Parents need psychological care because parents are with the child during the illness and their anxiety and behavior affect the sick child and the treatment process, and paying attention to the gender difference and the wishes of the couple can be a strategy to provide better services to the parents. And help the whole family